2009
DOI: 10.1007/s00586-008-0875-7
|View full text |Cite
|
Sign up to set email alerts
|

Allogenic versus autologous cancellous bone in lumbar segmental spondylodesis: a randomized prospective study

Abstract: The current gold standard in lumbar fusion consists of transpedicular fixation in combination with an interbody interponate of autologous bone from iliac crest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 40 publications
2
52
0
2
Order By: Relevance
“…Some studies have demonstrated that the use of iliac crest bone graft has substantial donor-site morbidity 6,7,16,17,[20][21][22][23] . However, other authors have reported that assessment of iliac crest donor-site pain is overestimated 15,24 and confounded by the concomitant pain from lumbar radiculopathy 17,18,25,26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have demonstrated that the use of iliac crest bone graft has substantial donor-site morbidity 6,7,16,17,[20][21][22][23] . However, other authors have reported that assessment of iliac crest donor-site pain is overestimated 15,24 and confounded by the concomitant pain from lumbar radiculopathy 17,18,25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Iliac crest autograft has been commonly used for achieving a fusion in lumbar spine surgery [3][4][5] . However, short and long-term morbidity associated with iliac crest bone-graft harvest is a concern to many surgeons and patients [6][7][8][9] .…”
mentioning
confidence: 99%
“…The principal merits of cancellous grafts are their safety, including a low risk of transplant rejection and disease transmission, and their excellent clinical success rate. However, the supply of donor bone grafts is restricted, and donor site morbidity increases if a larger autograft is harvested, in addition to other disadvantages, such as increased blood loss, potential wound infection and the prolonged anesthetic time [137,177]. In particular, although the incidence is low, complications associated with the harvesting of iliac crest bone, such as persistent postoperative pain and nerve/arterial injury, have been reported [170].…”
Section: Tissue Grafts Of Human Originmentioning
confidence: 99%
“…Based on a recently published protocol, 15 which is only briefly presented here, patients received an artifact-reduced CT (multidetector CT [MDCT] 16-Zeilen, Toshiba) of the index and superior adjacent segments for registration of implant-associated complications, such as migration, loosening, or nonunion (according to criteria published elsewhere 28 ), as well as for 3D measurement of the paravertebral muscles at 1 week and at 12 months after surgery.…”
Section: Data Collectionmentioning
confidence: 99%